ЎСПИРИНЛАРДА ИЛМИЙ ДУНЁҚАРАШНИ ШАКЛЛАНТИРИШНИНГ МУҲИМ ОМИЛЛАРИ - Шапсанова, Н.Б. (SCIENCE and SOCIETY, 2022)
This article discusses the laws of formation of worldview in adolescents, types of worldview, as well as the formation of scientific worldview in youth is a topical issue today.
Keywords: adolescent youth; worldview; globalization of information; manipulation; religious ideas; scientific ideas; information threats; scientific worldview; healthy psychology; commonality of being; society and man